Do People Get Used to Insulting Language? - Struiksma, Marijn E.; De Mulder, Hannah N. M.; Van Berkum, Jos J. A. (Frontiers in Communication, 2022)
Verbal insults go against a universal moral imperative not to inflict harm on others, and they also pose a threat to one’s face or reputation. As such, these ‘verbal slaps in the face’ provide a unique opportunity to explore the interface between language and emotion. We used electroencephalography (EEG) and skin conductance (SC) recordings to compare the short-term impact of verbal insults such as “Linda is an idiot” or “Paula is horrible” to that of more positive evaluations (e.g., “Linda is an angel”, “Paula is impressive”) and neutral factual descriptions (e.g., “Linda is a student”), examining how responses to these various speech acts adapt as a function of massive repetition. By using either the participant’s or somebody else’s name, we also explored how statement impact depended on who was being evaluated. Multilevel ERP analysis with three predesignated latency ranges revealed an early insult effect in P2 amplitude that was highly robust over repetition and also did not depend on who the insult was about. This P2 effect points to a very rapid and stable capture of emotional attention, plausibly triggered by the retrieval of evaluative word meaning from long-term memory. Insults also elicited a larger late positive potential (LPP), again regardless of who the insult was about, but this later effect did not withstand repetition. Skin conductance responses showed that insults did not lead to more arousal than compliments did. In all, our findings suggest that in a standard psycholinguistic comprehension experiment without real interaction between speakers, insults deliver lexical ‘mini-slaps in the face’, such that the strongly negative evaluative words involved (e.g., “idiot”) automatically grab attention during lexical retrieval, regardless of how often that retrieval occurs.